Treat them as buffalo : a novel - Yoxall, Blair Palmer (Algonquin of Chapel Hill/Little, Brown & Company, 2026)
"In 1885, Nikosis "Niko" Eriksen spends his days playing buffalo hunter, even though it's been many years since a member of his tribe has actually seen one of the once-ubiquitous animals. But when beloved Cousin goes missing, things start to fall apart. With law enforcement failing--indeed refusing--to investigate the disappearance, the community members take matters into their own hands, rallying around the leadership of a sawn-off shotgun-slinging rancher named Kate McCannon. The resultant women-led coalition of freedom fighters strikes back against the Mounted Police as they investigate the boys' disappearance and take their futures into their own hands. But violence continues to haunt Niko, and boys continue to disappear. As he leaves his boyhood behind and draws closer to finding Cousin, Niko's investigation points to a harrowing revelation about his own heritage, which heels closer to violence that any boy would wish to know."--Amazon.